2012
DOI: 10.1161/circheartfailure.112.969626
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and Complications After Implantable Cardioverter Defibrillator Therapy in Hypertrophic Cardiomyopathy

Abstract: P atients with hypertrophic cardiomyopathy (HCM) are at increased risk for sudden cardiac death (SCD), mostly caused by ventricular arrhythmias. SCD may occur as the initial presentation of HCM, often in asymptomatic or mildly symptomatic patients. 1 In fact, HCM is the most frequent cause of SCD in young people, including trained athletes. 2,3 Implantable cardioverter defibrillator (ICD) therapy may effectively terminate potentially life-threatening ventricular arrhythmias, thereby preventing SCD and prolongi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
125
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(141 citation statements)
references
References 36 publications
14
125
0
1
Order By: Relevance
“…51 Also, we would expect that this rate of excess ICDs in HCM patients, and SD rates, as well, will decrease further with emerging advances in risk stratification, including use of contrast-enhanced cardiovascular magnetic resonance. 36 Nevertheless, the sizeable proportion of young patients with device complications cited here and elsewhere [1][2][3][4]20,21,[24][25][26][27] contributes to the ICD decision-making dilemma, 52 in which the preservation of life is weighed against the not insignificant potential for inappropriate shocks and lead-related problems over long periods of time. Indeed, the device complication rate of 26% reported here exceeds by 1.7-fold our appropriate ICD intervention rate of 15%.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…51 Also, we would expect that this rate of excess ICDs in HCM patients, and SD rates, as well, will decrease further with emerging advances in risk stratification, including use of contrast-enhanced cardiovascular magnetic resonance. 36 Nevertheless, the sizeable proportion of young patients with device complications cited here and elsewhere [1][2][3][4]20,21,[24][25][26][27] contributes to the ICD decision-making dilemma, 52 in which the preservation of life is weighed against the not insignificant potential for inappropriate shocks and lead-related problems over long periods of time. Indeed, the device complication rate of 26% reported here exceeds by 1.7-fold our appropriate ICD intervention rate of 15%.…”
Section: Discussionmentioning
confidence: 92%
“…
However, the past 2 decades have witnessed the emergence of an expanded and effective risk stratification model, resulting in more reliable identification of those patients at increased SD risk, who may become candidates for the life-saving benefits of implantable cardioverter-defibrillators (ICDs), 1,9,11,13,[19][20][21][22][23][24][25][26][27] and advancements in heart transplantation, modern resuscitation techniques, and surgical management of outflow tract obstruction, as well. [9][10][11][12][13]23,23,[28][29][30][31] Whether these contemporary management options have resulted in reduced mortality rates for children and young adults with HCM is currently unresolved, and is the subject of the present clinical outcome investigation.
Methods
Patient Selection

Databases from 2 major HCM tertiary referral centers, Minneapolis Heart Institute Foundation and Tufts Medical Center, were accessed and 474 consecutive patients <30 years of age were identified presenting between 1992 and 2013.

…”
mentioning
confidence: 99%
“…The incidence of sudden death in HCM is low, around 0.7-1% per annum, and often young patients are affected (2). The use of implantable cardioverter-defibrillator (ICD) protects against SCD secondary to ventricular tachycardia (VT), ventricular fibrillation (VF), or bradycardia, with excellent results (3)(4)(5)(6)(7)(8). A major concern with ICD therapy is the delivery of inappropriate shocks, namely in response to supraventricular tachycardia and atrial fibrillation.…”
Section: Introductionmentioning
confidence: 99%
“…Prior observational studies have reported on the use of ICD therapy, including a meta-analysis which demonstrated rates of appropriate ICD interventions of 3.3% per year and inappropriate ICD interventions of 4.8% per year (6). However, a number of studies have been published since.…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate ICD interventions are believed to terminate arrhythmias, which otherwise might cause sudden cardiac death [10]. We noticed discrepancy in the number of adequate ICD interventions between two groups.…”
Section: Icd Interventionsmentioning
confidence: 78%